Muslims in a multi-religious society - Engineer, Asghar Ali (Economic & political weekly, 1990)
According to the author, the current controversy in India about Babri Masjid-Ramjanmabhoomi (in Ayodhya, Uttar Pradesh) which has caused lot of bloodshed is proof as to how relevant the past has become for the present conflict between Hindus and Muslims. He examines the situation of the Muslims in the country paying special attention to the conflict which developed between these two communities during the freedom struggle, Jawaharlal Nehru's commitment to secularism, manipulations of religious communities by the political parties, violence against Muslims etc